2020
DOI: 10.1186/s13059-020-1930-x
|View full text |Cite
|
Sign up to set email alerts
|

CUBIC: an atlas of genetic architecture promises directed maize improvement

Abstract: Background: Identifying genotype-phenotype links and causative genes from quantitative trait loci (QTL) is challenging for complex agronomically important traits. To accelerate maize gene discovery and breeding, we present the Complete-diallel design plus Unbalanced Breeding-like Inter-Cross (CUBIC) population, consisting of 1404 individuals created by extensively inter-crossing 24 widely used Chinese maize founders. Results: Hundreds of QTL for 23 agronomic traits are uncovered with 14 million high-quality SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 79 publications
0
62
0
Order By: Relevance
“…The trait mean values of culms for each accession (12 culms in 2014 and six culms in 2015 for each accession) were calculated. To reduce the effect of environment on phenotypic data, best linear unbiased prediction (BLUP) value for each trait was calculated based on the phenotypic data across two years using R package ‘lme4’ (Fang et al ., 2017; Liu et al ., 2020; Wang et al ., 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trait mean values of culms for each accession (12 culms in 2014 and six culms in 2015 for each accession) were calculated. To reduce the effect of environment on phenotypic data, best linear unbiased prediction (BLUP) value for each trait was calculated based on the phenotypic data across two years using R package ‘lme4’ (Fang et al ., 2017; Liu et al ., 2020; Wang et al ., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…We calculated the trait mean values of all the harvested culms for each accession in each year and then calculated the broad‐sense heritability ( H 2 ) as: H 2 = V G /( V G + V e / N ), where V G and V e represented genetic and residual variance, respectively; N was the number of years ( N = 2 in this study) (Liu et al ., 2020). The V G and Ve were estimated by treating genotype and environment as random effects in the mixed linear model.…”
Section: Methodsmentioning
confidence: 99%
“…We constructed 30 F 1 populations by crossing 1428 previously reported inbred lines from the CUBIC (Complete-diallel plus Unbalanced Breeding-derived Inter-Cross) synthetic population as a maternal pool [ 34 ] with 30 paternal testers from diverse heterotic groups. We performed genome-wide association studies (GWAS) on all populations to identify heterosis and trait-associated genes involved in maize improvement.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the lead SNPs were heterozygous and multiple haplotypes had been detected in the candidate regions, rendering it highly difficult to effectively identify favorable functional alleles. Moreover, previous research has shown that allelic heterogeneity may lead to misleading association and missing heritability (Yano et al ., 2016; Liu et al ., 2020). The haplotype information we provide here will thus be a valuable resource for future GWAS in tea plants.…”
Section: Discussionmentioning
confidence: 99%